Quality Assessment in Surgery- Conceptual Framework - Chowdhury, Abdullah Al Mamun; Hussain, Md Margub (Journal of Bangladesh College of Physicians and Surgeons, 2020)
‘Quality’ is a popular demand in health care. Surgeons as professionals are consistently putting their efforts to meet this demand. The standard and dimensions of ‘quality’ are changing and expectations are rising along with social reforms driven by scientific and economic growth. On the other hand, objective assessment of care in surgical patients is difficult and dependent on factors that are not precisely related to surgical skills. It is rather performance of all in the organization and sum of each and every human and system effort. In this effort we will discuss factors related to surgical care quality and different methods of assessment and their limitations. For quality surgical care, good intent, enabling environment with organized supportive system is required with skilled surgical team and meticulous monitoring system along the care process. J Bangladesh Coll Phys Surg 2020; 38(2): 93-97